PENGUJIAN BESARAN PERGESERAN LABA PERUSAHAAN MULTINASIONAL DENGAN MOTIV PERPAJAKAN DI ASEAN: STUDI FDI TIPOLOGI - Pratama, Rizki Adhi; Gunadi, Mohamad (Jurnal Akuntansi, 2024)
This study aims to examine the magnitude of outbound profit-shifting by multinational enterprises (MNEs) across different investment types in the ASEAN. Using ORBIS data from 2013 to 2018, a pooled least squares panel data analysis is conducted. Results indicate that investment activities aimed at achieving higher efficiency demonstrate greater elasticity regarding profit-shifting behavior. Notably, policymakers should focus on the manufacturing sector, where profit-shifting practices are more common in efficiency-seeking investments. Nevertheless, governments need to balance regulatory efforts and policies to attract foreign direct investment due to the potential benefits of FDI spillovers and the risks of profit-shifting activities. Achieving this balance is a critical challenge.